Effect of Particle Sizes and Contents of Surface Pre-Reacted Glass Ionomer Filler on Mechanical Properties of Auto-Polymerizing Resin - Naoyuki Kaga; Sho Morita; Yuichiro Yamaguchi; Takashi Matsuura (Dentistry Journal, 2023)
Herein, the mechanical properties of an auto-polymerizing resin incorporated with a surface pre-reacted glass ionomer (S-PRG) filler were evaluated. For this, S-PRG fillers with particle sizes of 1 μm (S-PRG-1) and 3 μm (S-PRG-3) were mixed at 10, 20, 30, and 40 wt% to prepare experimental resin powders. The powders and a liquid (powder/liquid ratio = 1.0 g/0.5 mL) were kneaded and filled into a silicone mold to obtain rectangular specimens. The flexural strength and modulus (n = 12) were recorded via a three-point bending test. The flexural strengths of S-PRG-1 at 10 wt% (62.14 MPa) and S-PRG-3 at 10 and 20 wt% (68.68 and 62.70 MPa, respectively) were adequate (>60 MPa). The flexural modulus of the S-PRG-3-containing specimen was significantly higher than that of the S-PRG-1-containing specimen. Scanning electron microscopy observations of the specimen fracture surfaces after bending revealed that the S-PRG fillers were tightly embedded and scattered in the resin matrix. The Vickers hardness increased with an increasing filler content and size. The Vickers hardness of S-PRG-3 (14.86–15.48 HV) was higher than that of S-PRG-1 (13.48–14.97 HV). Thus, the particle size and content of the S-PRG filler affect the mechanical properties of the experimental auto-polymerizing resin.